KOMODIFIKASI SENI RUPA DALAM BRANDING PARIWISATA BALI DI MASA KOLONIAL - Sindu Putra, Ida Bagus Komang (Studi Budaya Nusantara, 2021)
Bali island is very thick with arts and tourism. Balinese Fine Arts has gone through a long historical journey from the prehistoric era to the present. Many observers say that the art that has developed on the island of Bali has its own characteristics. Balinese Fine Arts as part of Balinese culture has its own complex development. When compared to the fine arts that have developed in other areas such as Yogyakarta, Bandung and Jakarta, Balinese art has a different ecosystem. In Balinese fine arts, the religious aspect is still very influential, in line with the flow of modernism brought by the entry of tourism that has occurred since the colonial period. Today, in Bali, art, which became present as an offering and is communal in a contextual context, continues and has become part of the traditions of the Balinese Hindu community in the midst of the development of modern / contemporary art which is personal and profane. In the context of artistry, Balinese fine arts to this day develop very dynamically where traditional art, as well as modern / academic art, develop and have their respective actors, enlivening the Balinese art ecosystem. The position of the Balinese art ecosystem that intersects with the development of the world of tourism is actually a potential that can be mobilized as Bali tourism branding. The purpose of this research is that the two of them can collaborate for mutually reinforcing developments. This research will be conducted using the literature method from existing data.